Processes and Techniques in Digital Marketing Analytics - Karanam, Sanjana; Shettar, Rajashree (International Journal of Computer Sciences and Engineering, 2020)
With the growing technologies and the dominance of digital media, the way companies market has changed and businesses are doing all they can to surpass their competitors. With the advancements in technology, as of 2019, 82% of businesses engage in digital marketing. With ever increasing data analysis tools and growth of statistical machine learning as a field, digital marketing channels have seen tremendous growth, and are now considered as an essential part of every company. Though each “company” carries out its analysis in their own way, there are five basic steps involved in digital marketing analysis. This paper presents the steps involved in the process of digital marketing analytics, along with their importance and the most prominent method in each step by exploring popular machine learning tools and proposes a general framework for digital marketing analytics.